Penerapan Metode ECOLA pada Pembelajaran Bahasa Indonesia untuk Meningkatkan Kemampuan Membaca dan Menulis Siswa Kelas 5 SDN Ragung 2 Sampang - Nur Muchlis, Fauziah; Hartiasih Soetomo, Risqi; Rahmawati, Arwani (Jurnal Cendekia Pendidikan, 2025)
The development of reading and writing skills are two important skills in learning Indonesian that are interrelated. However, in reality, elementary school students still experience difficulties in understanding the content of reading and writing coherently and clearly. The reading and writing skills of fifth-grade students at SDN Ragung 2 are still low because the learning methods used tend to be passive and do not involve students actively. Therefore, an integrative and enjoyable approach is needed, one of which is the ECOLA method which combines four language skills, namely listening, speaking, reading, and writing. This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which was implemented in two cycles. Each cycle consists of four stages, namely planning, action implementation, observation, and reflection. The subjects in this study were 14 fifth-grade students at SDN Ragung 2. Data collection techniques included observation, documentation, and tests. The instruments used included student observation sheets, student worksheets (LKS), and documentation of reading and writing results. The results showed an increase in students' reading and writing skills after the application of the ECOLA method. In cycle I, the average student score was 64.8 with a classical completion rate of 35.7%. After improvements to the learning process, in cycle II, the average score increased to 71.6 with a classical completion rate of 71.4%. This improvement demonstrates the effectiveness of the ECOLA method in Indonesian language learning to improve students' reading and writing skills in an integrated and meaningful manner.